Isolation and Identification of mould inhabiting plant rizosphere in Gunung Mutis Natural Reserve, East Nusa Tenggara - MUHAMMAD ILYAS (Biodiversitas Journal of Biological Diversity, 2006)
Indonesia as one of the megabiodiversity country has high biodiversity of plants, animals, and microbes. One of the microbeâ€™s biodiversity is mould inhabiting plant rhizosphere. Research and exploration on mould inhabiting plant rhizosphere in Gunung Mutis Natural Reserve, NTT has never been conducted before. The objective of the study was to isolate and identify mould inhabiting several horticulture and reforestation plants rhizosphere in Gunung Mutis Natural Reserve, NTT. The mould isolation method was based on direct inoculation. Theresult showed that eight moulds genera with several species variants had been isolated. The isolated moulds genera were; Aspergillus, Cephalosporium, Cunninghamella, Eupenicillium, Fusarium (2 species), Paecilomyces, Penicillium (5 species), and Trichoderma.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: mould, rhizosphere, Gunung Mutis Natural Reserve, East Nusa Tenggara (NTT), isolation, identification, direct innoculation